Acute oxalate nephropathy associated with Clostridiumdifficile infection. Issue 12 (5th December 2019) - Pandey, Deepali; Verma, Ashish; Ding, Yanli; Singh, Priyamvada; Magoo, Hemant
Abstract : Acute oxalate nephropathy has been associated with chronic diarrheal illness and only one case has been reported due to acute diarrhea secondary to Clostridium difficile colitis. To the best of our knowledge, this is the second case report of acute oxalate nephropathy due to C . difficile colitis. A 75-year-old man with a medical history of hypertension, type 2 diabetes mellitus, chronic kidney disease stage IV, recent C . difficile colitis was admitted for acute kidney injury with a creatinine (Cr) of 8.54 mg/dL (baseline Cr, 2.3–2.6 mg/dL). His urinalysis did not show any eosinophils, casts or crystals. Antinuclear antibody, antineutrophil cytoplasmic antibody, complement levels (C3 and C4) and hepatitis screen were negative; a renal ultrasound visualized no hydronephrosis. A kidney biopsy showed widespread tubular oxalate crystal deposition suggestive of hyperoxaluria as the cause of acute kidney injury. In conclusion, an acute diarrheal illness like C . difficile colitis can cause acute oxalate nephropathy.